Bullying, prejudice and school performance : a new approach - Crochick, José Leon ; Crochick , Nicole (Springer, 2020)
Contents: 1 Two Forms of School Violence : Bullying and Prejudice; 1.1 Social and Psychological Factors of Violence; 1.2 School Hierarchies and the Reproduction of Social Violence; 1.3 Bullying, Performance and Popularity; 1.4 Prejudice, Bullying and Authoritarian Personality; 1.5 Bullying, Authority and Autonomy; 1.6 Inclusive Education and the Fight Against School Violence; References; 2 Objectives and Research Method; 2.1 Objectives; 2.2 Method; 2.2.1 Participants; 2.2.2 Instruments; 2.2.3 Data Collection Procedures; References; 3 Analysis and Discussion of the Survey Data; 3.1 Relationships Among Perceived School Performance, Bullying and Prejudice; 3.1.1 School Performance and Violence-Self-evaluation; 3.1.2 School Performance and Violence-Peer Evaluation; 3.1.3 School Performance and Bullying; 3.1.4 School Performance and Prejudice; 3.2 Relationships Between Bullying and Prejudice and Adherence to the Ideology of Authoritarianism and Autonomy from the School Authority; 3.2.1 Relationships Between Bullying and Adherence to the Ideology of Authoritarianism; 3.2.2 Relationships Between Bullying and Autonomy from the School Authority; 3.2.3 Relationships Between Bullying and Prejudice; 3.3 Characteristics of the Perpetrators and Victims of School Violence, Individual Motivations for the Aggression and Feelings Caused in the Victims; 3.4 Hierarchies, Prejudice and School Violence Against Students in an Inclusive Situation; References; 4 Proposals for Addressing School Violence; References; Appendix: Research Instrument.